Minat Membaca Siswa Kelas VIII SMP Negeri 2 Talang Muandau Kabupaten Bengkalis Tahun Ajaran 2021/2022 - Karisma, Ayu; Nazirun, Nazirun (UIR Press, 2024)
This research was conducted because reading skills are very important in all aspects of life. Therefore, students must master reading skills well because these skills are directly related to their learning process. However, the results of interviews with Indonesian teachers at SMP Negeri 2 Talang Muandau show that students' interest in reading is still low. The purpose of this study was to describe, analyze, and interpret data about the reading interest of Grade VIII students of SMP Negeri 2 Talang Muandau in a systematic and detailed manner. This research uses a descriptive research type with a quantitative approach, with all eighth grade students as the population and research sample, and the sampling technique used is the Nonprobability technique, namely saturated samples. Data collection techniques include observation, questionnaires, and documentation. The results showed that overall, the eighth grade students of SMP Negeri 2 Talang Muandau had a good interest in reading Indonesian language textbooks, with the majority of students agreeing or strongly agreeing. Therefore, the initial hypothesis that students' interest in reading is low must be rejected.